Pengaruh deviden, hutang, harga saham terhadap profitabilitas pada perusahaan jasa subsektor transportasi - Kartika, Widya; Hasiholan Lumban Gaol, Ester; Damayanti Br Pandiangan, Sri (Jurnal Paradigma Ekonomika, 2021)
The purpose of the study being studied is to examine the impact of dividends, debt, share prices on profitability in the transportation sub-sector services on the IDX. The data collection method in this research is the sampling technique. The total specimens in the studied study were 6 specimens. The assessment technique used is the multiple linear regression techniques with multiple values. This study describes that dividend payments have a partial impact on profitability, as evidenced by the t value of 2.639> 2.055 and has a sig value of 0.014 <0.05. Deb to equity ratio has no impact on profitability, this can be seen from the t-count of -1,132 <2,055 and has a sig value of 0.268> 0.05. The share price has an impact on profitability, as evidenced by the t-count of -2.163 <2.055 and a significant value of 0.040 <0.05. The R2 test of 0.181 explains the weak relationship between the variable dividend payout ratio, debt to equity ratio, and share price on the profitability of 18.1%, and the remaining 81.9% is influenced by other factors. Â